Extracellular Vesicles From Adipose Tissue-Derived Stem Cells Affect Notch-miR148a-3p Axis to Regulate Polarization of Macrophages and Alleviate Sepsis in Mice - Bai, Xiaozhi; Li, Junjie; Li, Lincheng; Liu, Mingchuan; Liu, Yang; Cao, Mengyuan; Tao, Ke; Xie, Songtao; Hu, Dahai (Frontiers in Immunology, 2020)
Extracellular vesicles (EVs) from adipose tissue-derived stem cells have been reported to attenuate lipopolysaccharide (LPS) induced inflammation and sepsis while the specific mechanism is unclear. This study explored the underlying molecular mechanisms of EVs from adipose tissue-derived stem cells in reducing inflammation. LPS- induced macrophage models and mice model were established to mimic inflammation in vitro and in vivo. EVs were extracted from adipose tissue-derived stem cells and identified. It was found that proinflammatory cytokines, including IL-1β, IL-6 and TNF-α, substantially decreased after EVs were applied to LPS-stimulated macrophages and mice, and thus, LPS induced M1 polarization was inhibited and sepsis was strongly alleviated. In the LPS induced macrophages, the expression of Notch signaling molecules and the activation of the NF-κB pathway were substantially decreased after the administration of EVs. Then, RBP-J-/- mice and macrophages were used. It was found that the miR-148a-3p level was significantly lower in the RBP-J−/− macrophages than in the wildtype macrophages. In the LPS induced macrophages, the increasing of miR-148a-3p was milder in the RBP-J−/− macrophages than in the wild type macrophages. Then, miR-148a-3p was overexpressed in macrophages and mice, and we found that the expression of proinflammatory cytokines was increased both in vivo and in vitro. The protective effect of EVs in LPS induced sepsis was diminished by the overexpression of miR-148a-3p. In conclusion, we proved that EVs could attenuate inflammation and further protect organ function by regulating the Notch-miR148a-3p signaling axis and then decreasing macrophage polarization to M1.